Effect of Primary Health Care Expenditure on Universal Health Coverage: Evidence from Sub-Saharan Africa - Arhin K; Frimpong AO; Acheampong K (ClinicoEconomics and Outcomes Research, 2022)
Kwadwo Arhin,1 Albert Opoku Frimpong,2 Kwame Acheampong3 1Department of Economics, Ghana Institute of Management and Public Administration, Accra, Ghana; 2Department of Banking and Finance, University of Professional Studies, Accra, Ghana; 3Department of Accounting Studies Education, Akenten Appiah-Menkah University of Skills Training and Entrepreneurial Development, Kumasi, GhanaCorrespondence: Kwadwo Arhin, Department of Economics, Ghana Institute of Management and Public Administration, Accra, Ghana, Tel +233 246767908, Email arhinkwadwo@gmail.comBackground: Investment in primary health care (PHC) to achieve universal health coverage (UHC) and better health outcomes remains a key global health agenda. This study aimed to assess the effects of PHC spending on UHC and health outcomes.Methods: The study used the Grossman Health Production Model and conducted econometric analyses using panel data from 2016 to 2019 covering 34 countries in SSA. Fixed and random effects panel regression models were used for the analyses. All the analyses in this study were carried out using the statistical software package STATA Version 15.Results: We found that PHC expenditure has a positive significant but inelastic effect on UHC and life expectancy at birth and a negative effect on infant mortality. Both the fixed and random effects models provided a robust relationship between PHC expenditure and UHC and health outcomes. Education, access to an improved water source, and the age structure of the population were found to be strongly associated with health outcomes.Conclusion: The inelastic nature of the PHC expenditure means that the UHC goal might only be achieved at high levels of PHC expenditure. This implies that policymakers must make conscious effort to increase PHC expenditure to ensure the attainment of the UHC goal.Keywords: primary health care expenditure, universal health coverage, health outcomes, fixed effects, random effects, sub-Saharan Africa